Analisis Kadar Kadmium (Cd) dalam Bawang Merah Lokal Palu (Allium cepa L. var. aggregatum) pada Berbagai Lokasi dan Umur Tanam: Analysis of Cadmium (Cd) in Palu Local Shallots (Allium cepa L. var. aggregatum) at Various Locations and Planting Ages - Lindawati, Eka; Khairuddin, Khairuddin; Nurhaeni; Ruslan; Ridhay, Ahmad; Sosidi, Husain; Rahim, Erwin Abdul; Syamsuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
The local Palu shallot (Allium cepa L. var. aggregatum) plant is one of the leading products in the Central Sulawesi region. Shallots can experience a decrease in quality if they are contaminated with heavy metals, such as cadmium (Cd) in amounts that exceed the threshold. This study aims to determine the effect of planting age on cadmium levels in local Palu shallots cultivated in Oloboju Village and Solove Village, Biromaru District, Sigi Regency. The research variables used were the planting age which consisted of 4 levels (age 40, 50, 60, and 70 days), and the planting location which consisted of 2 levels (Solove Village and Oloboju Village). Cd levels were analyzed using an Atomic Absorption Spectrophotometer (AAS). Cadmium levels in shallot roots at two planting locations decreased with increasing planting age, from 101.34 - 107.18 mg/kg at 40 days of age to 1.68-3.78 mg/kg at 70 days of age. Shallot bulbs at two locations had lower cadmium levels than roots, namely 0.01-0.04 mg/kg. The results of the study found that planting time had a significant effect on cadmium levels in the roots of shallots, but planting age and planting location had no significant effect on cadmium levels in local Palu shallot bulbs with levels that met the SNI (Indonesian national standard) quality requirements